Solve for p 3.6p-p=m-0.4p

Math
3.6p-p=m-0.4p
Subtract p from 3.6p.
2.6p=m-0.4p
Move all terms containing p to the left side of the equation.
Tap for more steps…
Add 0.4p to both sides of the equation.
2.6p+0.4p=m
Add 2.6p and 0.4p.
3p=m
3p=m
Divide each term by 3 and simplify.
Tap for more steps…
Divide each term in 3p=m by 3.
3p3=m3
Cancel the common factor of 3.
p=m3
Simplify m3.
Tap for more steps…
Multiply by 1.
p=1m3
Factor 3 out of 3.
p=1m3(1)
Separate fractions.
p=13⋅m1
Divide 1 by 3.
p=0.3‾m1
Divide m by 1.
p=0.3‾m
p=0.3‾m
p=0.3‾m
Solve for p 3.6p-p=m-0.4p

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top